INTERACTION STUDIES OF GLIMEPIRIDE WITH SAMBILOTO HERBA EXTRACT AND ANDROGRAPHOLIDE, AND DIGITALIZATION OF PHARMACOKINETIC â PHARMACODYNAMIC DRUGS INTERACTION DATABASE - Rita Indriani, Lella
The prevalence of Diabetes Mellitus (DM) was predicted to reach 10,4% by 2040 with a mortality rate of 6%. The use of glimepiride, substrate CYP2C9, as oral antidiabetic is trending in Indonesia, but requires attention if used with inductors or inhibitors of CYP2C9 enzyme such as drugs or herbs. The change in the pharmacokinetics profile of glimepiride due to the modulation of its metabolic processes can predict the potential interaction. Digitized information or computerized decision support systems can be minimized the occurrence of drug interactions. Currently, the application of drug interactions with herbs in the Indonesian language is still limited. An application of drug interactions was developed with database sources collected from In Vitro-In Vivo Correlation (IVIVC) basic static model on CYP2C9 enzymes, research, and evaluation of glimepiride or CYP2C9 substrate interactions with herbal. Based on systematic review with search keywords in PubMed ((Herbal interaction) AND (2C9)), ((Herbs interaction) AND (2C9)) and in Google scholar "Herbal Interaction", "Herbs Interaction", and "inhibition CYP2C9", there are seven herbs namely sambiloto herb, mangosteen pericarp, pariah fructus, chili fructus, pomegranate, turmeric rhizomes, and ginger rhizomes. The best performs of the basic static model that will be used in the application was 1+Imax,u/Ki,u, R ?1.02 with the lowest RMSE, GMFE, PPE, and NPE values, true positive (TP) 84.62%, and true negative (TN) 85.71%. The research was conducted to evaluate the pharmacokinetics and pharmacodynamics interaction of co-administration of glimepiride 1 mg/kg with sambiloto herb extract 230 mg/kg on alloxan-induced diabetic rats. Glimepiride concentration in plasma was determined by validated LC-ESI-MS/MS system with positive ion mode m/z 491 ?126 (LOQ 2 ng/mL), whilst blood glucose levels with GOD-PAP. The result in diabetic rats showed additive pharmacodynamics interaction with higher AAC value 42.19% than a single administration of glimepiride (p<0.05) with a moderate risk level. Evaluation of interaction studies of glimepiride or other CYP2C9 substrates with chili fructus in diabetic rats and ginger rhizomes in diabetic rats and human showed additive pharmacodynamic interactions and antagonistic interaction alongside mangosteen pericarp in diabetic rats but did not show pharmacokinetic interactions. Turmeric rhizome and pomegranate showed additive pharmacodynamics interaction in diabetic rats and human, however pharmacokinetics interaction have only been showed in diabetic rats. The co-administration with a pariah fructus water extract shows a major risk level which led to mortality in diabetic rats and severe hypoglycemia in human.